Identifikasi bakteri enterik gram-negatif dan pola resistensi antimikroba pada burung psittacine yang dipelihara di Indonesia - Arfah Herawana El Zamzami; Safika; Mokhamad Fahrudin; Muhammad Piter Kombo; Wisnu Rahmadan Almanda (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2025)
Psittacines are vulnerable to bacterial diseases, including gram-negative infections. A key challenge in treating these birds is antibiotic resistance, where antibiotics become ineffective against the bacteria. This study aimed to identify gram-negative bacteria present in 11 fecal samples of psittacine from Taman Mini Indonesia Indah (TMII) in East Jakarta, as well as to determine the presence of antibiotic resistance in these bacteria. In this study, bacteria were isolated using MacConkey Agar media, followed by Gram staining and biochemical tests for bacterial identification. Antibiotic resistance testing was conducted using the Kirby-Bauer method against seven antibiotics. The results of bacterial identification showed the presence of Klebsiella sp., Proteus mirabilis, and Escherichia coli in the fecal samples of Psittacine from TMII. Resistance to the antibiotics nalidixic acid, doxycycline, tetracycline, gentamicin, erythromycin, cefotaxime, and trimethoprim-sulfamethoxazole was observed, with trimethoprim-sulfamethoxazole demonstrating the lowest resistance rate among fecal Psittacine bacteria.